'Calamity': the small town and railway as allegory. Issue 1 (2nd January 2019) - Ptáček, Luboš
Abstract: The aim of this text is to analyse and interpret the allegorical elements in the film Calamity by Věra Chytilová in 1981 in the context of contemporary social and existential situations; to describe individual elements of allegory; to prove that they are presented through different symbolic elements (specifically the ideological and artistic) which transform the relation of the allegorizing and the allegorized. The initial allegorical agents in the film Calamity are formed through the title of the film where the word 'calamity' produces three meanings: a natural phenomenon, a social (and implicitly political) situation and an existential crisis. Similarly, the small town and railway, as a space in which the most important part of the story occurs, create a synecdoche of the Czechoslovak society in the time of normalization and call attention to actual social and political crises linked with the normalization regime at the turn of the 1970s and 1980s. The specific political situation also creates a backdrop to the portrayal of the feminist viewpoint which the director conjoins with the fall of the patriarchal world. Finally, the film captures an existential crisis that is of an unpolitical and timeless character, shown predominantly through failures of human communication..